TANTANGAN DAN PELUANG ICT DALAM PENGELOLAAN PERENCANAAN ORGANISASI - Dinda Ravina; Muhammad Irwan Padli Nasution (JOURNAL SAINS STUDENT RESEARCH, 2025)
Key organizational planning in management is influenced by Information and Communication Technology (ICT). ICT provides fast access to information and analytical tools that support decision making. However, challenges such as system integration, data security, and lack of digital skills still hinder many organizations. This study uses a qualitative approach with secondary data analysis from industry reports and case studies. The results show that organizations that are able to overcome these challenges can gain competitive advantage. With the right strategy, ICT can improve efficiency and responsiveness in a dynamic market.